Primary tooth extraction with distraction behavior management techniques: A case report - Tanumiharja, Leonardo Jaya Setiadi; Apriani, Anie; Tanumiharja, Marvin Jaya Setiadi; Suwindere, Winny (Science Midwifery, 2026)
Treatment of primary teeth requires careful extraction and appropriate management to achieve optimal results and reduce the risk of complications. Distraction behavior management has been introduced as an important approach to address anxiety and improve patient cooperation during dental procedures, especially in pediatric patients. This case report describes an 8-year-old girl who underwent an extraction procedure using non-pharmacological distraction behavior management techniques. The results of extraction treatment with distraction behavior management proved to be appropriate, involving diverting the patient's focus from the instruments, the operator, and the procedure during the procedure. The extraction procedure proceeded smoothly from start to finish, despite the difficulty of primary tooth extraction. Primary tooth extraction is one of the most feared dental treatments for children. However, with appropriate behavior management techniques according to the child's behavioral classification, the tooth extraction procedure can proceed smoothly and without problems.